Current Chemotherapeutic Management of Patients with Gestational Trophoblastic Neoplasia. (11th May 2011) - May, Taymaa; Goldstein, Donald P.; Berkowitz, Ross S.
Abstract : Gestational trophoblastic neoplasia (GTN) describes a heterogeneous group of interrelated lesions that arise from abnormal proliferation of placental trophoblasts. GTN lesions are histologically distinct, malignant lesions that include invasive hydatidiform mole, choriocarcinoma, placental site trophoblastic tumor (PSTT) and epithelioid trophoblastic tumor (ETT). GTN tumors are generally highly responsive to chemotherapy. Early stage GTN disease is often cured with single-agent chemotherapy. In contrast, advanced stage disease requires multiagent combination chemotherapeutic regimens to achieve a cure. Various adjuvant surgical procedures can be helpful to treat women with GTN. Patients require careful followup after completing treatment and recurrent disease should be aggressively managed. Women with a history of GTN are at increased risk of subsequent GTN, hence future pregnancies require careful monitoring to ensure normal gestational development. This article will review the workup, management and followup of women with all stages of GTN as well as with recurrent disease.